Comparing nutritional value of diets among nutrition software - de Assunção, Lorraynne Barbosa; Schincaglia, Raquel Machado; Trindade, Daniella De Brito; Correia, Márcia Helena Sacchi; Peixoto, Maria do Rosário Gondim (Journal of Health Informatics, 2017)
Objective: To compare three nutritional calculation software regarding the agreement of nutritional composition, specifically the total energy of the diet, macro and micronutrients, totalizing 16 nutrients. Methods: Observational study that software evaluated were the DietWin Profissional®, Avanutri Online® and the World Food Dietary Assessment System®. Food Recall data from 100 children were used. The normality of the variables were verified using the Kolmogorov-Smirnov test. The results were analyzed using the Friedman and Tukey test, with a confidence level of 5%. Results: The nutritional calculations showed significant statistical differences in energy and fifteen nutrients: carbohydrates, proteins, lipids, saturated and monounsaturated fats, cholesterol, fiber, vitamins A, D, E and C, sodium, iron, calcium and zinc (p<0.05). The DietWin® program obtained the lowest values for the nutrients analyzed and the WorldFood® showed the highest values. Conclusion: The characteristic tables that make up the programs varied significantly in estimating values of nutrients.